Speed breeding: protocols, application and achievements - Blinkov, Andrey Olegovich; Kroupin, Pavel Yuryevich; Dmitrieva, Anna Ruslanovna; Kocheshkova, Alina Alexandrovna; Karlov, Gennady Ilyich; Divashuk, Mikhail Georgievich (Frontiers in Plant Science, 2025)
One of the limiting factors in breeding and genetic research is the time required to develop pure lines. This is due, on the one hand, to the prolonged vegetative period of a single generation and, on the other hand, to the specifics of inbreeding, which typically requires 4–6 consecutive generations of self-pollination in plant material. Researchers have always sought approaches that enable the rapid development of homozygous plant lines. Consequently, methods such as greenhouse cultivation during the autumn-winter period, single-seed descent, shuttle breeding, embryo culture, and doubled haploid technology have been introduced into practice. All these methods have both advantages and limitations. One of the latest approaches facilitating a significant reduction in the vegetative period of plants is speed breeding (SB). This method is based on the application of factors that shorten the time from sowing to flowering, as well as techniques that accelerate the generative phase of development and overcome postharvest dormancy. This review provides a comprehensive list and characterization of all factors that influence the efficiency of speed breeding to varying degrees. Among the factors discussed that reduce the sowing-to-flowering period are photoperiod, light sources, spectral composition and light intensity, temperature, carbon dioxide levels, vernalization, mineral nutrition, substrate volume, mechanical shoot removal, and the use of plant growth regulators. To shorten the generative phase, the review summarizes the application of embryo culture and forced desiccation of immature seeds, along with methods to overcome postharvest dormancy. Additionally, applications of genetic approaches and genetic engineering for shortening generation time in speed breeding are described. The review also consolidates detailed protocols for approximately thirty crops. The high efficiency of speed breeding in reducing both the vegetative period per generation and the time required to develop pure lines has led to its increasing adoption in various research fields. This review highlights the application of speed breeding for hybridization and pure line development, introgression of target alleles, and genomic selection. A list of phenotypic traits exhibiting high correlation between controlled-environment and field conditions is provided.